Developing English Workbook by Contextual Teaching and Learning for Third Grade of Junior High School - Alvin Fikrotuz Zakiah (Language-Edu, 2019)
AbstractThe existing of inappropriate English workbook for third grade students of Junior high school become main problem for the students. The existing of English Workbook has limited training and limited material for students. The aim of this study was to develop English workbook by contextual teaching and learning for third grade of SMP SIMANJAYA Lamongan. This study involves third grade students, English teacher, and two experts. The developing English workbook based on the need analysis and interview. The design of this study was Research and Development (R&D). The procedure of this study were, need analysis, writing a course grid, developing the product, try out the product and revising the final product. The instruments of this study is questionnaire. The data from the expert are analyzed and describe qualitatively. The try out is to know the whether it was appropriate and effective for students in third of Junior High school. The final product of this study is English workbook which using contextual teaching and learning. The result of this study showed that students were agree and interested in the learning process through this English workbook. Key words : English Workbook, contextual teaching and learning